IMS 1313-nanoparticle Mucosal Vaccine Enhances Immunity Against Avian Influenza and Newcastle Disease Viruses - Ismail, Nermeen M.; El-Deeb, Ayman H.; Emara, Mohamed M.; Tawfik, Hoda I.; Wanis, Nabil Abdel; Hussein , Hussein A. (International Journal of Poultry Science, 2018)
Background and Objective: Avian influenza and Newcastle disease viruses are a continuous threat to poultry industry. Vaccines are increasingly used to control these viral infections. This study aimed to develop efficacious vaccines and vaccination strategies against avian influenza and Newcastle disease viruses. Methodology: Two formulations of bivalent vaccines for avian influenza and Newcastle disease viruses were prepared based on the use of IMS1313-nanoparticles (mucosal vaccine) and Montanide ISA71 (parental vaccine) adjuvants. The prepared vaccines were delivered in specific pathogen free (SPF) chickens with different vaccination protocols. Cell mediated and humoral immune response (cytokine expression levels including IFN-γ and IL-6, lymphocyte proliferation, antibodies titers against both H5N1 and NDV) were measured. Challenge trial was carried out to determine the protection percent and shedding pattern of the challenged viruses. Results: Results of the present study revealed a significant increase of IFN-γ and IL-6 genes expression and lymphocytes proliferation in the vaccinated groups compared to the unvaccinated group. Two applications of the mucosal vaccine demonstrated higher hemagglutination inhibition (HI) titers and protection percentage ranged from 40-50% with different levels of virus shedding as measured by qRT-PCR assay. However, when the vaccines were applied in a prime-boost protocol (mucosal-parental, respectively), protection reached 90 and 100% against avian influenza virus (AIV) and Newcastle disease virus (NDV), respectively. No shedding of the NDV-challenge virus was detected whereas, AIV-challenge virus was detected in the samples of the 3rd day post-challenge. Conclusion: Indeed, the use of mucosal-parental vaccines in a prime-boost vaccination protocol demonstrated the potentiality of such approach.